Magnetic resonance and sonographic imagings of masticatory muscle myalgia in temporomandibular disorder patients. Issue 1 (February 2017) - Ariji, Yoshiko; Ariji, Eiichiro
Summary: This article reviews recently published studies investigating the MRI and sonographic diagnosis of masticatory muscle myalgia in temporomandibular disorder patients. The MRI and sonographic features of muscle after treatment are also discussed. Literature published within the last 15 years was obtained from the PubMed database using the following Mesh terms: magnetic resonance imaging (MRI) or sonography, masticatory muscle pain, and treatment. MRI and sonography enable accurate visualization and evaluation of the masticatory muscles, thereby increasing our understanding of pathology and cause of pain associated with these muscles. Although therapeutic efficacy is often evaluated based on clinical findings, MR and sonographic imaging studies may also be valuable.